The effect of regulations on port efficiency: an empirical study using regulatory quality and control of corruption index / Rudy Eruwan Jamain, Roza Hazli Zakaria and Nurulhuda Mohd Satar - Jamain, Rudy Eruwan; Zakaria, Roza Hazli; Mohd Satar, Nurulhuda (Research Management Institute (RMI), 2023)
A key determinant influencing port performance is the governance aspect. Since the port plays a crucial role in logistics supply chain systems, its performance determinants should be evaluated. Data from 57 ports worldwide was analysed to investigate how regulations affected their efficiency. First, we utilised the Data Envelopment Analysis (DEA) to obtain the measurement of the port’s technical efficiency. Then, the econometric estimation is used to examine the role of regulation on port’s technical efficiency. The findings from the econometric estimation suggests that Regulatory Quality (REGQ) and Control of Corruption (CORR) were positively correlated with the port’s technical efficiency One important contribution of the study is the implementation of DEA-L in the DEA measurement as to include the external variables in the analysis. This study suggests the government should improve the process by enhancing the application of high-technology items and digitisation that are able to ease the bottleneck at port.